Implementation of the Cepat Dekat Masyarakat Program in Bangilan District, Tuban Regency - Ahcmad Dwi Ilham Syafi’i; Tauran T; Tjitjik Rahaju; Indah Perabawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Population administration services are a form of public service that plays an important role in ensuring the fulfilment of citizens' civil rights. The Tuban Regency Government, through the Population and Civil Registration Office, launched the Cepat Dekat Masyarakat (CEDAK MAS) programme as an innovative service to bring population administration services closer to the community at the sub-district and village levels. This study aims to analyse the implementation of the CEDAK MAS Programme in population administration services in Bangilan Sub-district, Tuban Regency. The research method used is qualitative with a descriptive type. Data was collected through interviews, observations, and documentation, with informants consisting of officials from the Tuban Regency Population and Civil Registration Office, Bangilan Sub-district officials, village officials, and service users. Data analysis was conducted using the interactive model of Miles and Huberman, using George C. Edward III's policy implementation theory, which includes indicators of communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of the CEDAK MAS Programme in Bangilan Subdistrict has not been optimal. The main obstacles identified are uneven communication with the community, limited human resources and infrastructure to support services, and bureaucratic coordination that is not yet fully integrated. Nevertheless, the implementing apparatus has shown a good level of commitment in running the programme.